Features of localization coronary arterial orifices and angles of origin their proximal segments in usually formed hearts and with transposition of the great vessels. - Malov, A. E. (Морфологія / Morphologia / Morfologìâ, 2011)
The work purpose was revealing of features of localization coronary arterial orifices, angles of origin and a course of their proximal segments in usually formed hearts and with transposition of the great vessels. Research is executed on 31 specimens of usually formed hearts and 31 specimens with transposition of the great vessels. For the estimation of position the orifices in aortic sinuses and orientation of a course of proximal segments of coronary arteries the morphological researches was carried out. For the purpose of carrying out of the statistical processing, the obtained data has been presented on schematic images. As a result of research statistically authentic differences in localization distribution coronary arterial orifices on a vertical axis are established at a transposition of the great vessels, in comparison with usually formed hearts. Peculiarities of an arrangement orifices with acute angles of origin their proximal segments of coronary arteries and them intramural course are established.